1996
DOI: 10.1021/la9509763
|View full text |Cite
|
Sign up to set email alerts
|

Contact Angles for Liquid Drops at a Model Heterogeneous Surface Consisting of Alternating and Parallel Hydrophobic/Hydrophilic Strips

Abstract: Model heterogeneous surfaces consisting of alternating and parallel 2.55 μm hydrophobic and 2.45 μm hydrophilic strips were prepared on a gold film by patterning self-assembled monolayers of hexadecanethiol and mercaptohexadecanoic acid using an elastomer stamp. The advancing and receding contact angles were measured for liquid drops (distilled water, buffer solutions with pH = 8.0, 10.0, and 11.0, ethylene glycol, glycerol, and formamide) placed on this specially prepared surface. Contortion of the three-phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
173
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(196 citation statements)
references
References 19 publications
20
173
3
Order By: Relevance
“…As regards the global wetting properties, we believe that a simpler approach will suffice. This system has also been studied experimentally [4], mainly in the context of contact angles and Cassie's empirical law [29]. This law states that the contact angle θ of a macroscopic drop placed on a planar heterogeneous substrate satisfies…”
Section: Periodic Stripes a General Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards the global wetting properties, we believe that a simpler approach will suffice. This system has also been studied experimentally [4], mainly in the context of contact angles and Cassie's empirical law [29]. This law states that the contact angle θ of a macroscopic drop placed on a planar heterogeneous substrate satisfies…”
Section: Periodic Stripes a General Considerationsmentioning
confidence: 99%
“…Recent experimental and theoretical studies have shown that structured substrates exhibit a variety of novel adsorption properties which not only promise to be of importance to future technologies such as microfluidics [2], but are also of fundamental interest to statistical physics [3]. In particular, the effect of chemical inhomogeneities has been addressed recently in different contexts, for example: contact angles of liquid drops [4][5][6], droplet spreading [7], morphological phase transitions [8], three phase contact line [9], Cassie's law [10,11], drop shapes [12], construction of magnetic materials [13], microscopic packing [14], liquid channels [15], polymer blends [16,17], and dewetting [18], among others.…”
Section: Introductionmentioning
confidence: 99%
“…3 The optimization of the direct printing process of electronic structures requires knowledge and understanding of the equilibrium shape conformations of liquids on patterned surfaces. 7 For liquid features in the micron range, the surface to volume ratio is exceedingly large. Thus, the energetics associated with the boundary surface and interfaces determine the overall shape and stability of liquid microstructures.…”
Section: Introductionmentioning
confidence: 99%
“…• due to non-uniform contents or heterogeneous ma- terials (13) . The contact angle formed at the boundary of two kinds of liquids in a solid tube has also been reported to have speed dependence (14) .…”
Section: Comparison With Experimental Data and Discussionmentioning
confidence: 99%